The impact of the narrative mindset on effectivity in social problem solving. - Jerzy Trzebiński (Public Library of Science (PLoS), 2021)
The narrative mindset is a tendency to interpret social information in the frame of stories. Two experiments were conducted to determine if and why the narrative mindset increases social problem-solving effectivity. The experiments consisted of two parts: the experimental manipulation (inducing the narrative mindset or control condition) and the observation of effects. In the second part, presented as a separate study, a participant was asked to advise other people facing interpersonal problems (experiment 1) or emotional problems (experiment 2). Three pairs of coders judged each piece of advice independently on three scales: Effectivity of the advice, empathy, and personalization (using their own experiences in providing the advice). The results indicate that the narrative mindset increases empathy, supported by the co-occurring increase in the problem's personalization, which leads to higher effectivity. The results reveal the positive real-life implications of structuring social information within a story frame. It may encourage the introduction of the narrative mindset effects into an area of social cognition research. Finally, the experiments show that the narrative mindset may be activated experimentally, providing an effective instrument to test the impact of narrative knowledge on social cognition.